REDESCRIPTION OF IDANTHYRSUS BIHAMATUS (SABELLARIIDAE, POLYCHAETA): AN ENDEMIC SPECIES OF INDONESIA - Joko Pamungkas (BRIN Publishing (Penerbit BRIN), 2022)
The endemic polychaete species Idanthyrsus bihamatus is redescribed based on a new material collected from Bali, Indonesia. All key diagnostic characters of the genus were used to describe the species. Both photo– and SEM micrographs were used to illustrate the species. Additionally, a map was created to show the distribution of the species across the geographic region. The material of the present study is deposited at the Museum Zoologicum Bogoriense in Cibinong, Bogor, and is the first sabellariid collection of the museum.